Crystal Structure, Spectroscopic Investigations and Quantum Chemical Calculation Studies of (3aR,6S,7aR)-7a a Combined Experimental and Theoretical Studies - Alaşalvar, C.; Demircan, A.; Ko̧sar, B.K.; Pekacar, A.I.; Büyuk̈güngör, O. (Elsevier B.V., 2016)
The crystal structure and spectroscopic properties of (3aR,6S,7aR)-7a-bromo-6-methyl-2-[(4-methylphenyl)sulfonyl]-1,2,3,6,7,7a-hexahydro-3a,6-epoxyisoindole were determined by X-ray diffraction, IR and 13CNMR and 1H NMR spectroscopy techniques. We investigate molecular and crystal structure of the new sulfonamide, which was derived from an environmental friendly cyclization reaction in water. This work allow to the development of a stereo-selective tandem allylamine isomerization/Diels Alder cyclo-addition sequence led to rapid assembly of complex nitrogen containing heterocycles. The molecular geometry from X-ray determination, vibrational frequencies and NMR shifts values of the title compound in the ground state have been calculated by using CAM-B3LYP and B3LYP methods with 6-311++G(d,p) basis sets. The calculated results show that the optimized geometry can well regenerate the crystal structure and theoretical vibrational frequencies and chemical shift data are in good agreement with experimental data. Besides, it is examined nonlinear optic properties, molecular electrostatic potential map and HOMO-LUMO orbitals of the molecule. © 2016 Elsevier B.V.
Keywords: Crystal Structure; Cycloaddition; DFT; Environmentally Benign; IMDA; Sulfonamide